THE EFFECT OF USING RIDDLES GAMES ON STUDENTS’ VOCABULARY MASTERY ( A Study at the Seventh Grade Students of SMP Negeri 4 Padangsidimpuan in 2018/2019 Academic Year) - AYU ASHARI (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The aims of the research is to know the application of riddles games on students vocabulary mastery at the seventh grade students of SMP Negeri 4 Padangsidimpuan, to know before and after use riddles games on students vocabulary mastery at the seventh grade students of SMP Negeri 4 Padangsidimpuan, and to know whether there is any significant effect of riddles games on students vocabulary mastery at the seventh grade students of SMP Negeri 4 Padangsidimpuan 2018/2019 Academic Year. The population in this research is all of the seventh grade students of SMP Negeri 4 Padangsidimpuan are 340. The sample are 32 students which taken by purposive sampling. The research method is use by experimental method. Collecting data by observation sheet and test as an instrument. The result mean score of the application riddles games is 3.3, based on the technique of analysis data the criterion of score riddles games with categorized “Very Good”. To know the result of the data, the researcher analysis data by use the formula of ttest. The result of data analysis show that of ttest = 15.5, meanwhile ttable 2.04. It means that ttest is higher than ttable. So, the hypothesis is accepted. It means that there is significant effect of riddles games on students vocabulary mastery at the seventh grade students of SMP Negeri 4 Padangsidimpuan. Keywords: Riddles Games, Vocabulary Mastery